ENTERPRISE ARCHITECTURE DESA DIGITAL - Winarno, Winarno (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Village law no. 6 of 2014 is a trigger for villages to develop villages. Villages are given flexibility in developing the widest possible potential of the village. The village is trying to become a digital village, but there is no foundation architecture yet. Many villages are trying to develop information systems without creating an enterprise architecture first. In developing enterprise architecture, a framework is needed. The most suitable framework in the development of enterprise architecture is The Open Group Architecture Foundation (TOGAF). TOGAF can be used to build enterprise architecture in the village. Digital Village Enterprise Architecture that has been developed includes Business Architecture, Data Architecture, Application Architecture, Technology Architecture. Core business architecture is related to administrative services, complaints services, extension services, BUMDES and asset rental. The architecture application consists of 68 types of administration services, complaint applications, extension module applications, BUMDES applications and asset rentals. The data architecture is built according to integrated data modelling. As for architechture technology, it can be divided into two, namely backend technology and frontend technology.